Optimization air circulation in negative pressure closed-house poultry buildings: A study on evaporative cooling pad thickness and exhaust fan operating pattern - Lillahulhaq, Zain; Widodo, Wawan Aries; Sutardi, Sutardi; Yone, Thearith (Mechanical Engineering for Society and Industry, 2025)
An optimal environment for raising poultry requires a cool, humid climate. Negative pressure air circulation is widely implemented in closed-house cages, combined with evaporative cooling pads (ECP). Fresh air cannot naturally pass through the ECP due to the porosity of the material. The characteristics of the ECP and the configuration of the exhaust fan operating pattern affect airflow distribution, including velocity, temperature, and relative humidity (RH) levels. This research simulated the effect of varying ECP thickness on airflow distribution inside a closed-house cage. The simulation was run under 3D steady-state conditions with ECP thicknesses of 100 mm, 150 mm, 200 mm, and 300 mm, respectively. The ECP was kept wet, resulting in incoming air with 60% humidity and a temperature of 27 °C. The study used the K-ω SST turbulence model and SIMPLE second-order discretization. The analysis also provides recommendations for optimal exhaust fan operation during summer and identified restricted area. Five different fan operating patterns were tested, combining a small exhaust fan with two large ones. This analysis based on several parameter which refers uncomfortable environment, including: velocity, temperature, RH levels, and pollutant gas concentration. Hazardous conditions were determined by the maximum values observed across 42 iso-surfaces spaced 1 meter apart along the x-axis. A thicker ECP resulted in a higher pressure drop, reducing temperature differences inside the cage and leading to a more uniform temperature distribution. The 100 mm ECP thickness, the thinnest ECP layers, lowered the temperature inside the closed-house cage. The study suggests that, during summer, operating one small exhaust fan and one large fan is optimal due to the reduced presence of hazardous areas inside the cage.